2023
DOI: 10.1183/16000617.0259-2022
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for pneumothorax diagnosis: a systematic review and meta-analysis

Abstract: BackgroundDeep learning (DL), a subset of artificial intelligence (AI), has been applied to pneumothorax diagnosis to aid physician diagnosis, but no meta-analysis has been performed.MethodsA search of multiple electronic databases through September 2022 was performed to identify studies that applied DL for pneumothorax diagnosis using imaging. Meta-analysisviaa hierarchical model to calculate the summary area under the curve (AUC) and pooled sensitivity and specificity for both DL and physicians was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…One similar review study found a pooled sensitivity of 84% and specificity of 96% for the performance of DL for pneumothorax detection across all imaging modalities, in close agreement with our results. 40 Our study focused specifically on pneumothorax detection in CXRs (which are the first line imaging technique for pneumothorax) and used meta-regression to further evaluate several factors that may have an impact on performance. DL algorithms have also been developed to examine a variety of other common CXR pathologies, such as pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…One similar review study found a pooled sensitivity of 84% and specificity of 96% for the performance of DL for pneumothorax detection across all imaging modalities, in close agreement with our results. 40 Our study focused specifically on pneumothorax detection in CXRs (which are the first line imaging technique for pneumothorax) and used meta-regression to further evaluate several factors that may have an impact on performance. DL algorithms have also been developed to examine a variety of other common CXR pathologies, such as pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the deep learning model can automatically cover falsenegative cases that human experts may miss, helping to diagnose diseases. In a recent meta-analysis of deep learning for pneumothorax diagnosis, both sensitivity and speci city were improved by increasing the number of training samples 55 . However, there is a possibility of a high risk of bias, indicating that additional studies with participants or study designs to reduce this risk are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning techniques have been effectively applied in diagnosing pneumothorax (Sugibayashi et al 2023), aiding in the recognition and classification of its various forms. For traumatic pneumothorax, caused by physical damage to lung tissues, algorithms can automatically detect and localize the condition from CT images (Majkowska et al 2020, Tran et al 2021.…”
Section: Objectivesmentioning
confidence: 99%